Lack of Correlations between Electrophysiological and Anatomical‐Mechanical Atrial Remodeling in Patients with Atrial Fibrillation. Issue 5 (17th February 2015) - MAURY, PHILIPPE; THOMSON, EMILIE; ROLLIN, ANNE; BERRY, MATHIEU; COGNET, THOMAS; DUPARC, ALEXANDRE; MONDOLY, PIERRE; GAUTIER, MATHIEU; LAIREZ, OLIVIER; MÉJEAN, SIMON; MASSABUAU, PIERRE; CARDIN, CHRISTELLE; et al.
<x xml:space="preserve">Abstract</x> Background Atrial fibrillation (AF) progressively leads to electrical remodeling (ER) and anatomical‐mechanical remodeling (AR), whose relationships in humans remain poorly known. Methods ER and AR were compared in patients undergoing percutaneous radiofrequency (RF) ablation for AF. ER was defined by right and left appendage activation rates as a surrogate for atrial refractory periods. AR was approached by left atrial (LA) diameters and area and left atrial appendage (LAA) area and contractile function (mean emptying flow velocity) (LAAFV) before RF ablation. Mean duration between successive LAA contractions was considered as LAA mechanical rate. Results Forty‐one patients (31 men, age: 64 ± 9 years) with paroxysmal (27%), persistent (61%), or long‐persistent AF (12%) were prospectively included (ejection fraction: 44 ± 16%). Parameters exploring AR were highly correlated to each other: LA area (28 ± 7 cm2), LAA area (5.7 ± 2.25 cm2), LA transverse (49 ± 7 mm), and anteroposterior diameter (59 ± 13 mm) or LAAFV (29 ± 13 cm/s; P < 0.05 for each comparison). Parameters exploring ER were also highly correlated: right atrial appendage (RAA; 181 ± 39 ms) and LAA (176 ± 33 ms) activation rates (P < 0.0001). There was no significant correlation between any ER and AR parameter. Only LAA mechanical rate (174 ± 36 ms) was correlated to LAA or RAA activations rates (P ≤ 0.01). Conclusion ER and AR are not mutually related, atrial activation rate being not correlated to LA or LAA size or function. Thus, the mechanisms leading to AF‐induced atrial remodeling may differ for anatomical and electrophysiological aspects.